Design of prefabricated vertical drains considering soil disturbance. Issue 3 (June 2009) - Basu, D.; Prezzi, M.
Abstract : In the present study, the effect of soil disturbance on prefabricated vertical drain (PVD)-enhanced soft soil consolidation was studied using finite element (FE) analysis. Both square and triangular PVD installation arrangements were considered. The actual shapes of the PVD, disturbed zone and unit cell were preserved in the FE analysis. A parametric study for a wide range of possible hydraulic conductivity profiles with a sigmoidal shape indicated that the degree of disturbance in the immediate vicinity of the PVD and the extent of the disturbed zone are the two factors that significantly affect the consolidation rate. Proper evaluation of these factors is therefore necessary for satisfactory PVD design. A comparison was made between the degree of consolidation calculated using an analytical solution assuming a bilinear hydraulic conductivity profile and FE analysis assuming a sigmoidal hydraulic conductivity profile in the disturbed zone surrounding the PVD. The curves of degree of consolidation plotted against time factor that were obtained from these solutions were in reasonably good agreement. Based on the analytical solution, design charts for a variety of conditions and hydraulic conductivity profiles were developed. They can be easily used in practice to determine the required PVD spacing for the desired degree of consolidation and specified time. The design charts can also be used for conditions in which overlapping of disturbed zones occurs.